Biochar Production from Plant Residues: A Sustainable Approach for Carbon Sequestration and Soil Fertility Improvement - Anna Kaushik; P. Priyadharshini; S. Manimegalai; V. Palaniselvam; K. T. Parthiban (Archives of Current Research International, 2024)
This review article explores the sustainable practice of producing biochar from plant residues, effectively transforming green waste into a valuable resource commonly referred to as “green gold”. It discussed mainly on the pyrolysis process of biochar production, and the impact of different pyrolysis methods on the resulting biochar’s properties, including surface area, porosity, and nutrient holding capacity. Further, the review analyzes the multifaceted benefits of biochar for soil health and plant growth. It highlights how biochar can improve soil structure, increase water retention, and enhance nutrient availability, leading to healthier and more productive agricultural lands. Additionally, the review explores biochar’s potential in influencing the soil microbial community, potentially promoting beneficial organisms and suppressing harmful pathogens. It also explores biochar’s role in mitigating climate change by capturing and storing atmospheric carbon, effectively reducing greenhouse gas emissions. However, a balanced perspective is maintained by acknowledging potential drawbacks associated with biochar use, such as the need for further research to optimize production methods and potential negative impacts on certain soil fauna. This review highlights biochar’s promise as a sustainable, cost-effective solution for agriculture and environmental issues. Biochar adoption can lead to a greener future through carbon capture, soil health, and waste management.